Migration of Phthalates and Bisphenol A from Polyethylene Terephthalate Bottles into Beer During Storage at Controlled Temperatures - Krešimir Mastanjević; Brankica Kartalović; Dragan Kovačević; Vinko Krstanović; Kristina Habschied (Foods)
PET (polyethylene terephthalate) bottles contain different chemicals that can act as endocrine disruptors. Phthalates and bisphenol A can be found in various foods and beverages packaged in PET packaging or aluminum cans. For some phthalates, the European Union has established specified tolerable daily intakes for humans. This study aimed to establish the changes, types of phthalates (dimethyl phthalate, diethyl phthalate, diisobutyl phthalate, dibutyl phthalate, bis(2-ethylhexyl) phthalate, di-n-octyl phthalate), and bisphenol A concentrations in beer packaged in PET bottles and stored at two temperatures (4 °C and 20 °C) for four months. Beers were obtained from a local brewery after packaging into PET bottles and stored at the designated temperatures. GC-MS analysis was performed to determine phthalates and bisphenol A. Obtained data show that beers packaged in PET bottles can contain significant amounts of bisphenol A, and that their concentration increases with storage time. Phthalates were also identified in the samples, with the highest concentration of bis(2-ethylhexyl) phthalate found in the sample kept at 20 °C after 1 month of storage, sample P5; this concentration was 164.814 µg/L. BPA was recorded with the highest concentration in sample P11, which underwent 4 months of storage at a temperature of 20 °C.